Case Attraction on Infinitive Clauses of Ancient Greek: a case study on Herodotus, Plato and Xenophon - Geraldes, Caio Borges Aguida (2020)
In this dissertation we discuss the syntax of case attraction in the infinitive clauses of Ancient Greek, in which an constituent of the infinitive clause acting as the predicative of its subject has the case assigned from a matrix clause\'s argument, thus violating the prediction of locality. The main goal is to provide a strong account on the distribution of the phenomenon since the works on the topic from the 16th century to the current date did not dealt with this issue and assumed that the distribution was either random or related to arbitrary variables. At the first chapter, we present how the phenomenon appears and how it has been discussed in scholarly bibliography, including both the older philological accounts and the modern minimalist discussions concerning it. The second chapter presents the reader to the selection of texts used as a corpus (Herodotus, Plato and Xenophon) and the criteria employed to analyse the data thereby gathered. We show at the third chapter the quantitative analysis of the distribution of case attraction in relation to variables previously considered to be correlated to it and to the variables linguistically expected to be so. Lastly at fourth chapter we further discuss the implications of our distributional findings to our comprehension of the phenomenon in Ancient Greek, particularly on pragmatic and semantic grounds, as well as its relation to similar phenomena cross-linguistically. We argue that although optional, the case attraction is favoured by environments where the target of attraction holds preeminent pragmatic or semantic functions, a tendency known to interact with similar phenomena in other languages displaying double outcomes of agreement.